Liquefaction of Helium and the Promotion of National Science - Ede, Andrew (Scientia Canadensis, 1990)
ABSTRACTIn 1923 John McLennan and his assistants succeeded in the liquefaction of helium. This event was heralded by the Canadian media as a major triumph of science. Yet it was neither a scientific first, nor a terminal experiment, but simply a means of producing material for use in McLennan's cryogenic research program. This article examines the events surrounding the liquefaction as they related to McLennan's efforts to promote national science and establish a post-war national science council.